ACCOUNTING INFORMATION SYSTEM AND INTELLECTUAL CAPITAL SUPPORT SUSTAINABLE DEVELOPMENT OF MANAGEMENT - vienda A. Kuntjoro (MEDIA STUDI EKONOMI, 2016)
Purpose – The purpose of this paper is to recognize the importance of sustainable development of management in firms that is based human resource development activities whereas accounting information system as tools to do data processing with capability of intellectual capital that fit it from certain discipline may drawn quality of life of one country. Design/methodology/approach – this study uses meta-analysis as the explanation approach as finding out the performance of accounting information system with capability of intellectual capital both as the bridges to sustainable development of management through human resource development activities whereas automatically quality of life of one country can be drawn and it may necessary be approved by empirical study for the next future research. Finding – Accounting Information System and Intellectual Capital both will produce the information standards that will be performed by human resource development activities that result on the sustainable development of management than can be fully implemented. Originality/value – The accounting information system and intellectual capital value to perform knowledge that brings quality of life in one country can be counted through human resource development activities to contribute sustainable development of management and all  those characteristics have different kind of situation will affect different information standard that can  be proved by empirical study. Keyword : accounting information system, intellectual capital, human resource development, sustainable development of management.